Tác động của hệ thống kinh doanh thông minh đến hiệu suất cá nhân: Vai trò điều tiết của lãnh đạo chuyển đổi - Nguyễn Trọng , Phương; Nguyễn Kim, Nam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
Business intelligence (BI) system has recently garnered significant attention due to their ability to improve both organizational and individual performance. This study aims to analyze the impact of BI system quality on individual performance through the mediating role of management accounting system (MAS) usage. Additionally, this study investigates the moderating role of transformational leadership (TL) in the relationship between BI system quality and MAS usage. The study uses a convenience sample of 326 management accountants. SmartPLS software is used to analyze the data. The results show that the components of BI system quality, including system quality, information quality, support service quality, and data quality, have an impact on MAS usage, which in turn indirectly affects individual performance. In addition, transformational leadership plays a moderating role in the relationship between BI system quality and MAS usage. Based on these findings, the study offers significant managerial implications for both theory and practice, aiming to improve individual performance in the context of BI system application.
Keywords: Management accounting; Individual performance; System; Business intelligence